Numerical Analysis of Mechanical Behavior Using Bio-Compatible Material for Dental Prosthesis - Dogar, Ayesha A. (2024)
Recent technological advancement has revolutionized the field biomedical engineering and has significantly enhanced the well being of human life. From the design and manufacturing of bio-compatible materials to the development of software for computer-aided design (CAD) modeling and simulation, biotechnology plays a crucial role in creating safe and effective dental implants. Finite element analysis has been accustomed to simulating the stresses and strains on implants helping to optimize the design and insertion process. This study aims to compare the stress profiles of Polyetheretherketone (PEEK) and Titanium alloy dental implants during different stages of implant insertion depths. The study builds bone-blood interface CAD models and performs numerical simulations. The results indicate that PEEK is potentially capable of replacing Titanium alloy as a suitable material for dental implants. Additionally, the study evaluates von Mises stresses in cortical and cancellous bone and considers the impact of torque and insertion depth on stress profiles, as well as strain and deformation calculations. The results provide an insigt into the usage of biocompatible materials in dental implants.